Unravelling the structure of First John: Exegetical analysis, Part 1 - Bigalke, Ron J. (HTS teologiese studies, 2013)
Surveying commentaries and introductions to the Johannine epistles reveals a multiplicity of methodology with regard to the structure of the epistles. Proposals have generally emphasised characteristics of content (doctrine and paraenesis), style (antithesis and repetition) or outline divisions. If the intent of the author is connected to the structure of the text, commentaries and introductions may not adequately discern the authorial intent. The lack of agreement amongst commentators as to the division of the First Epistle of John has resulted in numerous interpretative conclusions. As a consequence of difficulty in ascertaining the structure of the text, interpretations are frequently formulated upon theological persuasions and historical reconstruction. The purpose of the article is to overcome such persuasions and reconstructions.